ALAT EVALUASI PEMBELAJARAN PEMBUATAN POLA BUSANA TAILORING - Irna Kurnia; Pipin Tresna P (Fesyen Perspektif, 2016)
Evaluation is a process which aims at giving consideration to determine the quality of something. Specifically, learning evaluation aims to measure the students’ understanding of the material being taught. The evaluation result cannot be separated from the teacher's ability to plan, implement, manage, and report it in accordance with the correct evaluation procedure and the learning objectives. Therefore, learning evaluation tool for clothing patterns tailoring aims to design, verify, validate, and analyze the results of the evaluation tool for clothing patterns tailoring. The evaluation tool was in the form of a table of assessment rubric with some certain criteria and assessment aspects which are appropriate with the learning objectives of tailoring. Since the evaluation tool focuses on the learning process of making men's suits, the assessment rubric consists of some aspects related to the development of the patterns of men’s suits. The validation which were performed on evaluation and material experts indicate the eligibility of evaluation tool for learning process of making men's suits. The percentage of “proper” category based on the evaluation expert is 90.08%, while the percentage of “proper” category based on the material expert is 97.5%.